The Integral Role of School Culture in Shaping Student Behavior and Attitudes: A Case Study of Elementary School - Dewi Widiana Rahayu; Sadun Akbar; Sri Untari; Hari Wahyono (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the influence of school culture on student behavior and attitudes at Antawirya Krian Elementary School. Recognizing its significance, the research examines how various elements such as philosophy, organizational structure, facilities, vision, mission, and procedural rules shape this dynamic. A qualitative case study approach was employed, using observations, interviews, and documentation for data collection. Data analysis through a phenomenological perspective offered a thorough understanding of the school's cultural practices. The findings highlight the principal's crucial role in embedding the school's philosophy, which combines religious and Javanese cultural values, through consistent communication and exemplary behavior. The school's organizational structure promotes democratic values and management transparency, essential for achieving its objectives. Although the facilities are not perfect, their maintenance ensures a conducive learning environment. The vision and mission focus on developing well-rounded students with strong moral values and a global perspective, reinforced through both curricular and extracurricular activities. School culture is evident in practices such as morning recitations and communal activities, fostering a sense of community and respect among students. The involvement of the entire school community, including teachers and students, is vital in maintaining a positive school culture. Teachers serve as role models and educators, while students actively uphold school values. The study emphasizes the importance of collaboration among all school stakeholders in optimizing character education and enhancing educational quality. The roles of the principal, organizational structure, and community practices are identified as key factors in cultivating a positive school culture, ultimately improving character education and overall educational quality at Antawirya Krian Elementary School.